Pengembangan Sistem Pemantau Kebocoran Gas Elpiji dan Peringatan Dini Bahaya Kebakaran Berbasis Internet of Things - Husny Husny; Freddy Kurniawan; Lasmadi Lasmadi (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2022)
The fire hazard due to an LPG cylinder explosion can be triggered from a gas cylinder leak. Not infrequently these incidents lead to loss of life and property loss. This study proposes the design of an LPG gas leak monitoring system and early warning of fire hazards. The system is designed to be integrated with the internet network through the Internet of Things (IoT) platform. The MQ-6 sensor module is used to detect LPG gas leaks and a fire sensor to detect fire. The sensor is installed close to the gas outlet source to ensure gas leakage and fire. The data from the sensor is read by the microprocessor and sent to the web server via the interface device. When the concentration of LPG gas in the air exceeds a certain level or a fire is detected, the microprocessor gives a command to turn on the alarm and sends a hazard notification to the smartphone. Hazard notifications, gas concentrations and status of hazard conditions can be accessed in real-time on Android-based smartphones. The results of the tests that have been carried out show that this system can provide information on hazard notification messages and gas concentration values in the range of 1000 - 10000 ppm. The fire detector in this system can detect fires up to a distance of 110 cm from the source of the fire. Then, hazard notifications and gas concentration levels can be accessed via a smartphone with the Kodular web application in the form of a real-time graphic display.